Biotechnology Biosensors, Biomaterials and Tissue Engineering Annual Volume 2023 - Jesús Villarreal-Gómez, Luis (Biomedical Engineering, 2023)
Biomedical technology is continually changing, and new approaches are being developed daily. Although widely used, conventional solutions are losing efficacy due to the evolution of microorganisms and the environment. Pathologies and diseases negatively affect humans and animals, but nanotechnology appears promising in the diagnosis and treatment of a variety of health conditions. This book examines some of these nanotechnologies, discussing their advantages and limitations. It is organized into four sections and includes ten chapters that address such topics as drug delivery systems for cancer treatment, photodynamic and photothermal treatments for bacterial infections, electrospun fibers for nanomedical applications, monoclonal antibodies, nanotheranostics, and much more.